Manajemen Diklat Guru dalam Era Digital - Nindya Azzahrah; Khansa Arista Widya Maulida; Ibnu Qital Pasaribu (STIKes Ibnu Sina Ajibarang, 2024)
Education and training management in the digital era involves various aspects, from planning, implementation, to effective evaluation. Training planning must be responsive to teacher needs and the latest technological developments. The implementation of training must utilize digital platforms that allow flexibility in time and place, as well as interactive and collaborative learning methods. Training evaluation must be carried out on an ongoing basis using digital tools to ensure consistent improvement in teacher competency.